Redescription of Parapercis punctata (Cuvier, 1829) and status of Neosillago Castelnau, 1875 and its type species Neosillago marmorata Castelnau, 1875 (Perciformes: Pinguipedidae) - Ho, Hsuan-Ching (Zootaxa, 2013)
The status of two doubtful fish species is reviewed. Percis punctata Cuvier, 1829 is confirmed to be a valid species of Parapercis Bleeker, 1863 and a senior synonym of Parapercis guezei Fourmanoir, 1966. A redescription of Parapercis punctata is provided, based on four specimens collected from the western Indian Ocean. Examination of the holotype of Neosillago marmorata Castelnau, 1875 revealed that Neosillago is a junior synonym of Parapercis and N. marmorata is a junior synonym of Parapercis nebulosa (Quoy & Gaimard, 1825).